Analysis of the implementation of policies on the development of Indonesian migrant workers’ families in the field of economic empowerment in Kupang city - Welin, Elisabeth; Kase, Petrus; Nursalam, Nursalam (Goodwood Publishing, 2021)
Purpose: This research aims to analyze the implementation of policies on developing Indonesian migrant workers’ families in the field of economic empowerment in Kupang city. Research methodology: The method used in this research is a qualitative research method with a case study approach. Results: The implementation of the family empowerment program for Indonesian workers is going well. This is supported by the existence of good communication, the availability of information and human resources, the influence of the position, and organizational arrangements to run the program in accordance with the SOP. Limitations: This research only analyzes the implementation of policies on the development of Indonesian migrant workers’ families in the field of economic empowerment in Kupang city. Contribution: This research becomes scientific information for public administration science.